Testing a bedside personal computer clinical care classification system for nursing students using Microsoft Access. - Feeg VD; Saba VK; Feeg AN (CIN: Computers, Informatics, Nursing)
This study tested a personal computer-based version of the Sabacare Clinical Care Classification System on students' performance of charting patient care plans. The application was designed as an inexpensive alternative to teach electronic charting for use on any laptop or personal computer with Windows and Microsoft Access. The data-based system was tested in a randomized trial with the control group using a type-in text-based-only system also mounted on a laptop at the bedside in the laboratory. Student care plans were more complete using the data-based system over the type-in text version. Students were more positive but not necessarily more efficient with the data-based system. The results demonstrate that the application is effective for improving student nursing care charting using the nursing process and capturing patient care information with a language that is standardized and ready for integration with other patient electronic health record data. It can be implemented on a bedside stand in the clinical laboratory or used to aggregate care planning over a student's clinical experience.